Electroacupuncture to improve post-stroke cognitive function and modulate cerebral iron deposition: a randomized controlled trial protocol using MRI - Sun, Ning; Xie, Fang; Wang, Zhe-Tao; Liu, Yi-Wei; Yang, Hui-Lin; Chen, Lei; Lu, Jing-Kang; He, Yi; He, Cheng-Qi; Liu, Sha-Xin (Frontiers in Neurology, 2026)
BackgroundPost-stroke cognitive impairment (PSCI) is common and hampers rehabilitation. Dysregulated iron homeostasis and ferroptosis are implicated in PSCI, yet targeted treatments are lacking. Acupuncture may improve cognition, but its early-intervention efficacy and iron-related mechanisms remain unclear.Methods and analysisThis single-blind randomized controlled trial will enroll 72 patients with ischemic stroke-related cognitive impairment (IS-CI). Participants will be randomized 1:1 to electroacupuncture (EA) or sham electroacupuncture (sEA) in addition to standard pharmacotherapy and rehabilitation. Participants in the EA group will receive verum stimulation at Baihui (GV20), Sishencong (EX-HN1), Shenting (GV24), and bilateral Neiguan (PC6), along with five adjunct points—Hegu (LI4), Zusanli (ST36), Xuanzhong (GB39), Sanyinjiao (SP6), and Taichong (LR3)—on the affected side. The sEA group will receive sham acupuncture at non-acupoint, non-meridian locations situated 1–2 cun away from the true acupoints. Interventions are delivered 5 times weekly for 4 weeks (20 sessions, 30 min each). The primary outcome is the change in Montreal Cognitive Assessment (MoCA) score from baseline to week 4. Secondary outcomes include Mini-Mental State Examination (MMSE), Modified Barthel Index (MBI), Hamilton Anxiety (HAMA) and Depression (HAMD) scales, Pittsburgh Sleep Quality Index (PSQI), and PSCI incidence at 3-month post-stroke (MoCA <26). A prespecified MRI substudy (n = 30) will use 3.0 T quantitative susceptibility mapping (QSM) to quantify regional cerebral iron and explore associations between changes in susceptibility and cognitive measures. Participants and outcome assessors are blinded; allocation is concealed; analyses will follow prespecified statistical plans.ConclusionThis trial is designed to evaluate the effects of EA on cognitive function in patients with IS-CI and to explore whether changes in cognition are accompanied by changes in cerebral iron deposition measured by QSM. It aims to assess the feasibility and preliminary effects of this intervention and to explore iron-related mechanisms in PSCI using an imaging approach.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, ITMCTR2025001739.